Developing an aquaponics system to learn sustainability and social compromise skills - Duarte, Abel José (2015)
The goal of this project, one of the proposals of the EPS@ISEP Spring 2014, was to develop an Aquaponics System. Over recent years Aquaponics systems have received increased attention since they contribute to reduce the strain on resources within 1st and 3rd world countries. Aquaponics is the combination of Hydroponics and Aquaculture, mimicking a natural environment in order to successfully apply and enhance the understanding of natural cycles within an indoor process. Using this knowledge of natural cycles, it was possible to create a system with capabilities similar to that of a natural environment with the support of electronics, enhancing the overall efficiency of the system. The multinational team involved in the development of this system was composed of five students from five countries and fields of study. This paper describes their solution, including the overall design, the technology involved and the benefits it can bring to the current market. The team was able to design and render the Computer Aided Design (CAD) drawings of the prototype, assemble all components, successfully test the electronics and comply with the budget. Furthermore, the designed solution was supported by a product sustainability study and included a specific marketing plan. Last but not least, the students enrolled in this project obtained new multidisciplinary knowledge and increased their team work and cross-cultural communication skills.